Recruitment and Talent Management in the Era of Artificial Intelligence - Vohra, Tanvi (2022)
Artificial intelligence as a phenomenon is emerging in the economical and organisational context for it enables firms to accomplish their tasks in a faster and more efficient way. AI is seen as a powerful tool in the human resource department, wherein it enables HR professionals in delegating their administrative tasks and provides them with time to focus on other business strategies. This qualitative research study was conducted to analyse the perception of human resource professionals on the adoption of artificial intelligence tools in the recruitment and talent management functionalities of an organisation. Since it is the decision of human resource professionals to ascertain when and on what tasks this delegation of AI tools is necessary, it was important to gather information from their corporate experiences. Considering the aim behind this research study, semi-structured interviews were conducted with human resource professionals of various organisations. The data collected from these interviews established that artificial intelligence is being readily accepted by the human resource department, although they do not have complete reliance on such tools, for the HRD is a people-centric sector, wherein there a constant human intervention is required. The primary data gathered from interviews suggested that irrespective of its numerous benefits, artificial intelligence tools cannot substitute the flexibility, generativity, and adaptability associated with human resource professional’s experience.